Mobility Improvements Are Found in Older Veterans After 6 Months of Gerofit Regardless of Body Mass Index Classification - Addison, Odessa (J Aging Phys Act, 2019)
Veterans represent a unique population of older adults, as they are more likely to self-report a disability and be overweight or obese compared with the general population. We sought to compare changes in mobility function across the obesity spectrum in older veterans participating in 6 months of Gerofit, a clinical exercise program. A total of 270 veterans (mean age: 74 years) completed baseline, 3-, and 6-month mobility assessments and were divided post hoc into groups: normal weight, overweight, and obese. The mobility assessments included 10-m walk time, 6-min walk distance, 30-s chair stands, and 8-foot up-and-go time. No significant weight × time interactions were found for any measure. However, clinically significant improvements of 7–20% were found for all mobility measures from baseline to 3 months and maintained at 6 months (all ps <05). Six months of participation in Gerofit, if enacted nationwide, appears to be one way to improve mobility in older veterans at high risk fordisability, regardless of weight status.